End of Meeting Report - ISPC 7 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
The seventh ISPC meeting was attended by 79 participants from 25th to 27th March 2013. The report annexes contain the list of participants as well as the final agenda for the meeting.